Flavonol Tri-O-glycoside and Other Chemical Constituents from Flowers of Aristolochia trulliformis - Holzbach, Juliana C. [UNESP] (2019)
A new flavonol triglycoside, named kaempferol-3-O-β-D-glucopyranosyl-(1→4)-a-L-rhamnopyranosyl-(1→6)-β-D-glucopyranoside, was isolated from flowers of Aristolochia trulliformis (Aristolochiaceae) together with 15 known compounds, including six flavonoids and four lignans. The structures of the compounds were determined by spectroscopic analyses, including 1D and 2D nuclear magnetic resonance (NMR) techniques and high-resolution mass spectrometry (HRMS).